Effective healthcare teams require effective team members: defining teamwork competencies - Leggat Sandra G (BMC, 2007)
Abstract Background Although effective teamwork has been consistently identified as a requirement for enhanced clinical outcomes in the provision of healthcare, there is limited knowledge of what makes health professionals effective team members, and even less information on how to develop skills for teamwork. This study identified critical teamwork competencies for health service managers. Methods Members of a state branch of the professional association of Australian health service managers participated in a teamwork survey. Results The 37% response rate enabled identification of a management teamwork competency set comprising leadership, knowledge of organizational goals and strategies and organizational commitment, respect for others, commitment to working collaboratively and to achieving a quality outcome. Conclusion Although not part of the research question the data suggested that the competencies for effective teamwork are perceived to be different for management and clinical teams, and there are differences in the perceptions of effective teamwork competencies between male and female health service managers. This study adds to the growing evidence that the focus on individual skill development and individual accountability and achievement that results from existing models of health professional training, and which is continually reinforced by human resource management practices within healthcare systems, is not consistent with the competencies required for effective teamwork.